Next Generation Sequencing (NGS) in Personalized Medicine: Emphasizing Public Health Beyond Reality - Vikas Pandey; Mohinee Kumari (Recent Trends in Infectious Diseases, 2025)
NGS is a modern technology that allows researchers to quickly sequence large amounts of DNA or RNA, it is also known as massively parallel sequencing or deep sequencing. NGS has revolutionized genomic research and biological sciences by its speed, scale, accuracy, ultra-high throughput, and cost. NGS replaced the conventional sequencing method. A novel idea in healthcare is precision medicine, which involves adjusting medical care to each patient’s unique traits and behaviors. Precision medicine improves therapeutic response with minimal side effects due to genetic, environmental, and lifestyle factors. By utilizing advanced tools, like NGS, clinicians, can identify specific mutations, tailor treatment strategies, predict treatment outcomes, and monitor disease progression more effectively in diverse patient populations. This personalized approach holds promise for managing chronic illnesses, predicting disease susceptibility, guiding preventive measures, and improving overall patient outcomes. This paper explores the concept of precision medicine, its applications, problems, and potential advances. A novel idea in healthcare is precision medicine, which involves adjusting medical care to each patient’s unique traits and behaviors. Precision medicine improves therapeutic response with minimal side effects due to genetic, environmental, and lifestyle factors. This paper explores the concept of precision medicine, its applications, problems, and potential advances.
Keywords: Genomic Research; Next-Generation Sequencing (NGS); Precision medicine; disease prediction; personalized healthcare